2009
DOI: 10.1088/1752-7155/4/1/017101
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene levels in the exhaled breath of 200 healthy pupils within the age range 7–18 years studied using SIFT-MS

Abstract: The published results of breath isoprene studies, to date largely involving adults, are briefly reviewed with special attention given to the work done on this topic during the last 10 years using selected ion flow tube mass spectrometry, SIFT-MS. Then the new data recently obtained on isoprene levels in the exhaled breath of some 200 healthy children and young adults (pupils) with ages ranging from 7 to 18 years measured using SIFT-MS are presented in detail. A concentration distribution has been constructed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 28 publications
(64 reference statements)
10
82
2
1
Order By: Relevance
“…Recently, some studies have identified groups of volatiles and other biomarkers in COPD patients that have potentially useful relationships to cell degradation processes. There are several analytical detection approaches available, including gas chromatography-mass spectrometry (GC-MS) [1][2][3][4][5][6][7], proton transfer reaction-mass spectrometry (PTR-MS) [8][9][10][11], selected ion flow tube-mass spectrometry (SIFT-MS) [12][13][14][15][16][17][18], ion mobility spectrometry (IMS) [2,[19][20][21][22][23][24][25][26][27][28], and electronic noses [29][30][31][32][33] as well as other types of sensors [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have identified groups of volatiles and other biomarkers in COPD patients that have potentially useful relationships to cell degradation processes. There are several analytical detection approaches available, including gas chromatography-mass spectrometry (GC-MS) [1][2][3][4][5][6][7], proton transfer reaction-mass spectrometry (PTR-MS) [8][9][10][11], selected ion flow tube-mass spectrometry (SIFT-MS) [12][13][14][15][16][17][18], ion mobility spectrometry (IMS) [2,[19][20][21][22][23][24][25][26][27][28], and electronic noses [29][30][31][32][33] as well as other types of sensors [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…There are several analytical detection approaches available for human breath investigations, including gas chromatographymass spectrometry (GC-MS) [1][2][3][4][5][6][7], proton transfer reactionmass spectrometry (PTR-MS) [8][9][10][11], selected ion flow tubemass spectrometry (SIFT-MS) [12][13][14][15][16][17][18] and ion mobility spectrometry (IMS) [2,[19][20][21][22][23][24][25][26][27][28] and electronic noses [29][30][31][32][33] and different types of sensors [34][35][36][37][38][39][40]. The sampling techniques include direct sampling, partly using sample loops [41][42][43][44], Tedlar bags [45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…Using an analogous line of argument, exercise scenarios on an ergometer support the idea that some peripheral (muscle) tissue may play a role in isoprene synthesis. While this contrasts previous work postulating a purely hepatic origin of isoprene [15,50], the above modeling study provides interesting new perspectives on the age dependence of isoprene output [49,47,34] as well as its reduction under statin therapy [24,50]. Furthermore, it opens up the possibility for a mechanistic interpretation of future experimental findings and challenges new hypotheses.…”
Section: Practical Implicationsmentioning
confidence: 66%